Factors associated with premenstrual symptoms: a study among graduate-level students of the institute of science and technology, Tribhuvan university - Srisa Rijal; Gauri Shrestha (BMC Women's Health)
Abstract Background Premenstrual Symptoms (PMS) refer to the psychological, physical, and behavioral symptoms that appear during the luteal phase of menstruation, impacting the day-to-day activities of females. Methods This study employed institutional-based cross-sectional research methods. Data were gathered from all female participants at the Institute of Science and Technology, Tribhuvan University, and only 285 female participants fulfilled the inclusion criteria. The data were collected using a self-administered questionnaire to assess demographic, socio-economic, lifestyle habits, and menstrual health-related factors, as well as to measure premenstrual symptoms. A standard tool, the Premenstrual Symptoms Screening Tool (PSST), was used for this purpose. Depression, Anxiety and Stress Scale (DASS-21) was used to measure the psychological distress. Factors associated with PMS were analyzed using Multiple Binary Logistic Regression. Result Among the 285 participants, 40% reported experiencing Premenstrual Symptoms. The most common physical symptoms were joint or muscle pain (56.49%), breast tenderness (45.26%), abdominal pain (44.91%), acne flare-ups (40.35%), and fatigue (35.09%). The factors such as age at menarche, participants with dysmenorrhea, participants who consume menstrual delaying medicine and participants having mild, moderate and severe stress were found to be significant at a 5% level of significance with the Premenstrual Symptoms. Conclusion The factors associated with Premenstrual Symptoms are stress, menstrual delaying medicine, dysmenorrhea, and the age at menarche of participants. The result indicates the necessity of women’s health programs, psychological support, and access to counseling in academic environments.